User Acceptance For Complaint Management System In Multimedia College - Azimah, A. Rahim (2008)
Complaint Management System (CMS) has become an integral player in any organization ability to expand services to its community. This system is very new system to staff and student in Multimedia College (MMC). The objective of having this system in MMC is to centralize all complaint from MMC community. Other that that, it provides a common channel to report any unsatisfied situation or problem to daily activities such as PC problem, unclean toilet, air conditioning malfunction, and so on. Having said this, the system has yet to be evaluated in terms of user acceptance. As a result, the top management of MMC has no information as to what extent the system is being accepted among the target users. Thus, this study aims to evaluate the user acceptance of the system. In order to achieve this, a survey was carried out on users of CMS. The survey was done using a customized QUIS with 4 sections and 17 questions. Out of one thousand seven hundreds and seventy nine (1779) users, only one hundred and forty four (144) questionnaire has been distributed to six (6) group of users identified by random sampling and only one hundred and twenty five (125) are received back from the selected user. Overall findings shows that all sections have been rejected by all group of users, except for position of message on screen and system speed. This study concludes that the system has to be upgraded to be fully utilized by the users.